THE ROLE OF SCHOOL ADMINISTRATORS IN PROMOTING EDUCATIONAL MANAGEMENT FOR LEARNERS SKILL IN THE 21ST CENTURY OF SCHOOL UNDER THE NAKHONRATCHASIMA PRIMARY EDUCATION SERVICE AREA OFFICE 6 - Phanitloet, Chayaphon; Poophayang, Piangkae (Journal of MCU Nakhondhat, 2021)
The Objectives of this research article were 1) to study the role of school administrators in promoting educational management for students to develop skills in the 21st century of schools under Nakhon Ratchasima Primary Educational Service Area Office 6 2) To compare opinions about the role of school administrators in promoting education management to provide learners with skills in the 21st century classified by school administration experience 3) to study recommendations on the role of school administrators Further education: Promote education management to enable learners to acquire 21st century skills as a survey research The sample consisted of 123 people by simple randomization and 9 key informants. Questionnaires were tools for collecting data. There is a .965 confidence factor and a structured interview. The statistics for data analysis were percentage, mean, standard deviation. The research results were found that 1) The role of the school administrators of the schools under the Nakhon Ratchasima Primary Educational Service Area Office 6 overall was at a high level. 2) The results of comparing opinions of school administrators, roles in promoting educational management of the learner skills in the 21st century of the Sorting House under the Nakhon Ratchasima Primary Educational Service Area Office 6, classified by school administration experience. The overall difference was statistically significant at the .01 level. 3) Recommendations for the role of school administrators in promoting education management in order to provide learners with 21st century skills. In learning and innovation Teachers should be encouraged to educate and create innovations for use in the teaching and learning of information, media and technology. Teachers should be encouraged to use up - to - date information in teaching and learning management. Life and career skills Should promote the teaching and learning in parallel.